Dispute Settlement Model of Land Acquisition for Public Interest - Bokings, Julia Citra Riski (Damhil Law Journal, 2022)
This study aims to analyze obstacles in resolving conflicts over land acquisition for public interest in Pohuwato Regency, as well asformulatethe ideal model for resolving conflicts over land acquisition for the public interest in Pohuwato Regency. This type of research uses empirical research, by using a statutory approach, a conceptual approach, and a case approach. Sources of data used are primary data and secondary data. The data that has been completed is analyzed using qualitative descriptive. Based on the research results that have been described, there are several findings in this study, namely (1)There are obstacles in resolving conflicts over land acquisition for public interest in Pohuwato Regency. The first obstacle is related to legal factors where in terms of legal substance, there is a regulation on the use of consignments as a safe-keeping of compensation private law provisions which shift to public law provisions. And the second obstacle is the determination of compensation, which should be based on an agreement with the land owners, turned out to be unilaterally determined by the Land Procurement Committee. estimate the amount of compensation for the holders of land rights.(2) The ideal model for resolving conflicts over land acquisition for the public interest in Pohuwato Regency, namely the non-adjudication settlement model, namely through deliberation where all parties involved carry outactivities that involve listening to each other, giving and receiving mutual opinions, as well as a desire to reach an agreement on the form and amount of compensation and other issues related to land acquisition activities on a voluntary basis. As well as a settlement model by adjudication or through a court route, where the Court has the authority to decide the amount and form of loss given to the holder of land rights whose rights are affected by land acquisition for development in the public interest.